An interim report on "subjectivization" and "objectivization" of administrative law: Book review of Luis Medina Alcoz, Libertad y autoridad en el derecho administrativo. Derecho subjetivo e interés legítimo: una revisión, Madrid, Marcial pons, 2016 - Doi, Tsubasa (P.A. Persona e Amministrazione, 2023)
The interplay between rights and the public interest is a crucial issue in administrative law. Recent developments in Germany and France regarding the "objectivization" or "subjectivization" of administrative litigation have brought this issue to the forefront. In his book, "Libertad y autoridad en el Derecho administrativo," Luis Medina Alcoz offers an invaluable perspective on administrative law in France, Italy, Germany, and Spain, tracing its evolution from the 19th century to the present and emphasizing the importance of the concepts of rights within the administrative law system. Its sharp insights and broad scope make it a significant contribution to the field. However, this paper explores the book's significance from a different angle. By examining the arguments that the book does not fully address and the underlying assumptions it makes about key concepts, this paper will demonstrate that the book not only describes a possible conception of administrative law, but also raises numerous important issues for further academic inquiry.